2018
DOI: 10.1007/s10922-018-9460-5
|View full text |Cite
|
Sign up to set email alerts
|

Report on the 10th International Conference on Autonomous Infrastructure, Management, and Security (AIMS 2016)

Abstract: AIMS 2016 focused on the theme ''Management and Security in the Age of Hyperconnectivity''. The AIMS conference positions itself in the network management community as an educational venue for young researchers and Ph.D. students. The AIMS program included keynotes, technical sessions and Ph.D. Workshop sessions, but also hands-on labs and an educational panel for training & Remi Badonnel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…At the end of the exhaustive examinations, it was revealed that K-Means could help identify malicious flow. [16] In a research titled Management and Security in the Age of Hyperconnectivity, the authors revealed that the emergence of Self-Organizing Network (SON) has helped increase the proliferation of threats such as botnet and also helped solve this loophole, a concept known as Network Element Virtual Temperature (NEVT) to create the needed stability in the Network Elements (NE).Similarly, [17] proposed a detection technique for mobile botnet, which focused on static code analysis, considering permissions and API calls. The static analysis provides a lightweight approach as compared to the dynamic analysis.…”
Section: Related Literaturesmentioning
confidence: 99%
“…At the end of the exhaustive examinations, it was revealed that K-Means could help identify malicious flow. [16] In a research titled Management and Security in the Age of Hyperconnectivity, the authors revealed that the emergence of Self-Organizing Network (SON) has helped increase the proliferation of threats such as botnet and also helped solve this loophole, a concept known as Network Element Virtual Temperature (NEVT) to create the needed stability in the Network Elements (NE).Similarly, [17] proposed a detection technique for mobile botnet, which focused on static code analysis, considering permissions and API calls. The static analysis provides a lightweight approach as compared to the dynamic analysis.…”
Section: Related Literaturesmentioning
confidence: 99%